ANALISIS PENERAPAN STRATEGI PEMASARAN PERALATAN PELABUHAN DENGAN MENGGUNAKAN PENDEKATAN ANALISIS SWOT PADA PT TOWIN INNOVEN - Nanda Bella Prisdina; Mujtabah Fatururrahman (POLITEKNIK LP3I JAKARTA, 2023)
This research is motivated by the increasing number of companies engaged in contractors. The number of competitors who market the same product also has an impact on sales at PT Towin Innoven. Marketing strategy is an important part of implementing a business. The formulation of the problem in this study is how the marketing strategy of port equipment with the SWOT technique at PT. Towin Innoven? which aims to find out how the results of the SWOT analysis in the marketing strategy at PT Towin Innoven. In this study, the type of qualitative research is descriptive. Because in this study also to determine the external and internal conditions of the company. In this case the researcher uses data collection techniques such as: observation, interviews and documentation and uses data triangulation techniques to compare the results of the data in the study. The technical tool used is swot analysis. The results shown by the SWOT analysis diagram show that the company is in quadrant I, namely the SO (Strength Opportunity) strategy which supports an aggressive strategy (growth oriented strategy). This is a very profitable situation for the company. Where, the company has the power so that it can take advantage of existing opportunities.Â Keywords: Marketing Strategy, SWOT Analysis, Port Equipment.